Facebook Profile Pictures: Gender Differences in Frequency and Type of Profile Pictures Posted within One-Year Period Among Older Adults - Fiebert, Martin S.; Liner, Laura (Advances in Social Sciences Research Journal, 2017)
This study examines gender differences between the frequency and the types of profile pictures posted on Facebook within a twelve-month period among adults aged fifty or over. The purpose of this study is to follow-up on previous research conducted by the Facebook Research Group at California State University, Long Beach (CSULB), which consisted of a younger sample (Fiebert, Castaneda, Pham, McGivern, Caudillo, & Warren, 2017). The method of data collection and analysis closely replicated the previous study. Profile pictures were categorized into one of four groups: 1) self in close-up; 2) self in long shot; 3) self with group; 4) other. In congruence with the previous study, this study found that women changed their profile pictures significantly more frequently than men. However, in contrast to the previous study, this study found that the most commonly posted profile picture for both genders is self with group, and the least common profile picture posted for both genders was self in long shot.